Heavy metals accumulation in Hertia cheirifolia along the highway in Setif region, Algeria - Amina Belguidoum; Takia Lograda; Messaoud Ramdani (Society for Indonesian Biodiversity, 2020)
Abstract. Belguidoum A, Lograda T, Ramdani M. 2020. Heavy metals accumulation in Hertia cheirifolia along the highway in Setif region, Algeria. Biodiversitas 21: 2786-2793. The aim of this work was to study the possibility of using Hertia cheirifoia spontaneous plant, generally present in uncultivated environments, as an indicator of pollution. The aerial parts of ten H. cheirifolia populations were collected along the East-West highway. Sampling is carried out in areas considered polluted or low contaminated in the region of Setif. Nine metallic trace elements concentrations (Pb, Zn, Cu, Fe, Mn, Cd, Ag, Bi, and Sb) were determined, for each population, by Atomic Absorption Spectrophotometry with Flame (AASF). Statistical analyzes were performed using mainly box and whisker diagrams, principal component analysis, and UPGMA. The concentrations detected for contaminants (MTE), in general, were very high, far exceeding international certified standards. The MTE concentrations in different populations were calculated for each metal and a positive correlation is observed. The order of MTE in the plant was found as follows: Fe > Zn > Mn > Pb > Sb > Cu > Bi > Ag > Cd. The Fe concentrations are very high in H. cheirifolia with an average of 3600 ± 1491.5 mg/kg. The populations of H. cheirifolia have shown a significant capacity to accumulate heavy metals. The presence of metal ions in the aerial parts of the plant designates that H. cheirifolia is a super accumulator of MTE and can be used as a bioindicator, which opens up prospects for its application to soils phytoremediation.